Building fast and selective Zn ion channels for highly stable quasi-solid-state Zn-ion batteries - Kao, Chun-Chuan; Liu, Jiahao; Ye, Chao; Zhang, Shao-Jian; Hao, Junnan; Qiao, Shi-Zhang (Journal of materials chemistry. A, Materials for energy and sustainability, 2023)
Quasi-solid-state Zn-ion batteries (QSSZIBs) with gel electrolytes hold practical promise to deliver a high energy density because of their high safety and ionic conductivity of gel electrolytes. However, the sluggish and the low selectivity of Zn ion transportation leads to unsatisfactory cycle life of QSSZIBs. Herein, a Zn ion channel was constructed by confining the gel electrolyte in intercalated halloysite nanotubes. The resultant Zn ion channels show fast and highly selective Zn ion transportation and therefore suppress hydrogen evolution, Zn dendrite growth and formation of Zn 4 SO 4 (OH) 6 · χ H 2 O during cycling. The QSSZIBs exhibit an excellent Zn plating/stripping coulombic efficiency of ∼99.7% in 400 cycles and over 1600 h cycle life at a current density of 1 mA cm −2 and a corresponding areal capacity of 1 mA h cm −2 . Building Zn ion channels for fast and selective Zn ion transportation can direct development of QSSZIBs with high cycling stability. Based on the aforementioned advantages, the assembled Zn/i-HNTs@PAM/I 2 full battery exhibits an exceptionally long cycle life of 8000 cycles at a high current density of 8 C. Ordered ion channels constructed by confining a gel electrolyte in intercalated halloysite nanotubes exhibit fast and selective Zn ion transportation and therefore enhance the cycling stability of the quasi-solid-state Zn-ion batteries.